À propos de vestiges humains immatures inédits provenant des niveaux moustériens de Qafzeh - Patrice Courtaud; Anne-Marie Tillier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Several seasons of excavations at the Mousterian site of Qafzeh have produced many human remains, of both adults and children (Vandermeersch 1981, Tillier 1999). Four human bones were recently inventoried in the collections at the Institut de Paléontologie Humaine in Paris. Their inventory reference QH3 (i.e. Qafzeh 3) could lead to the supposition that they came from Neuville’s first discoveries. This material consists in fact of immature bones and their possible attribution to individuals already known is discussed. The immature bone sample already known (MNI = 8, Tillier ibidem) might incorporate two of the newly inventoried bones: a coracoid process (part of the Qafzeh 21 child) and a middle hand phalanx (probably belonging to Qafzeh 22). By contrast two left metatarsi (second and third) could represent an additional individual, older than Qafzeh 21 (ca. 3 yrs old at death) and younger than Qafzeh 4 (ca. 7 yrs old).